From Unlearning to Relearning: Practitioners’ Integration of Children's Indigenous Knowledge for Language Development in Contemporary Early Childhood Classrooms - Mahan, Sibongile (Universitas Jambi, Magister Program of English Education Department, 2025)
Indigenous Knowledge Systems (IKS) have been a part of South African culture for generations. However, due to Eurocentric views that deemed them inferior to Western knowledge, the education system has largely overlooked them. As a result, literacy was primarily associated with formal schooling, while home-based literacy practices were marginalized. This study set out to explore how early childhood practitioners incorporate children’s IKS which depend heavily on oral and hands-on transmission into language development in preschools. The research involved three multilingual preschools in a Gauteng township, with fifty children and six practitioners participating. Using site visits, observations, field notes, audio recordings, and informal conversations, the study gathered qualitative data, guided by Vygotsky’s social constructivist theory. Analysis revealed inconsistent and informal use of children’s IKS, with educators selectively drawing on cultural knowledge and predominantly recognizing only the most widely spoken languages. This sidelined children from minority linguistic backgrounds. The study concluded that purposeful integration of IKS is an effective teaching strategy in preschools, helping children engage in multiple languages, revitalize marginalized tongues, and embrace their dynamic multilingual identities. The research coincided with a period of major reform in South Africa’s early childhood education sector, which is moving toward greater professionalization. As universities now offer training modules like Resource Development for Early Childhood Educators, practitioners are becoming better equipped to integrate IKS into multilingual teaching by creating and using culturally relevant materials.